Risk Stratification Tools and Prognostic Models in Non-muscle-invasive Bladder Cancer: A Critical Assessment from the European Association of Urology Non-muscle-invasive Bladder Cancer Guidelines Panel - Soukup, Viktor; Čapoun, Otakar; Cohen, Daniel; Hernández, Virginia; Burger, Maximilian; Compérat, Eva; Gontero, Paolo; Lam, Thomas; Mostafid, A Hugh; Palou, Joan; van Rhijn, Bas W G; Rouprêt, Morgan; et al. (European urology focus, 2020)
CONTEXT: This review focuses on the most widely used risk stratification and prediction tools for non-muscle-invasive bladder cancer (NMIBC). OBJECTIVE: To assess the clinical use and relevance of risk stratification and prediction tools to enhance clinical decision making and counselling of patients with NMIBC. EVIDENCE ACQUISITION: The most frequent, currently used risk stratification tools and prognostic models for NMIBC patients were identified by the members of the European Association of Urology (EAU) Guidelines Panel on NMIBC. EVIDENCE SYNTHESIS: The 2006 European Organization for Research and Treatment of Cancer (EORTC) risk tables are the most widely used and validated tools for risk stratification and prognosis prediction in NMIBC patients. The EAU risk categories constitute a simple alternative to the EORTC risk tables and can be used for comparable risk stratification. In the subgroup of NMIBC patients treated with a short maintenance schedule of bacillus Calmette-Guerin (BCG), the Club Urológico Español de Tratamiento Oncológico (CUETO) scoring model is more accurate than the EORTC risk tables. Both the EORTC risk tables and the CUETO scoring model overestimate the recurrence and progression risks in patients treated according to current guidelines. The new concept of conditional recurrence and progression estimates is very promising during follow-up but should be validated. CONCLUSIONS: Risk stratification and prognostic models enable outcome comparisons and standardisation of treatment and follow-up. At present, none of the available risk stratification and prognostic models reflects current standards of treatment. The EORTC risk tables and CUETO scoring model should be updated with previously unavailable data and recalculated. PATIENT SUMMARY: Non-muscle-invasive bladder cancer is a heterogeneous disease. A risk-based therapeutic approach is recommended. We present available risk stratification and prediction tools and the degree of their validation with the aim to increase their use in everyday clinical practice.
Keywords: Bladder cancer; Recurrence; hodnocení rizik; Europe; Models, Statistical; Progression; Scoring system; invazivní růst nádoru; Risk stratification; lidé; statistické modely; Evropa; urologie; Risk Assessment; společnosti lékařské; prognóza; Societies, Medical; Scoring model; Urology; směrnice pro lékařskou praxi jako téma; Urinary Bladder Neoplasms; nádory močového měchýře; Practice Guidelines as Topic; Prognosis; Risk; Neoplasm Invasiveness; Humans